196k views
3 votes
(2, 1), (-3,6) find the distance

2 Answers

6 votes
Answer: 7.07 units

Explanation: Use the distance formula d=the square root of ((x2-x1)^2+(y2-y1)^2). Plug in the values accordingly:
d= square root of ((-3-2)^2+(6-1)^2)
Simplify:
d= square root of ((-5)^2+(5)^2)
d= square root of (25+25)
d= square root of (50)
d= 7.07 units
User Nachtigall
by
5.6k points
6 votes

Answer:

10

Explanation:

User Carmenism
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.